IMPLEMENTASI MULTIPLE INTELLIGENCES RESEARCH (MIR) DALAM PENGELOMPOKAN KELAS DAN PEMBELAJARANNYA(STUDI KASUS DI MIM PK KARTASURA TAHUN AJARAN 2015/2016) - Fauzi, Arfan Rifqi (2016)
This study aims to determine (1) Implementation of grading is based on Multiple Intelligences Research (MIR) in MIM PK Kartasura the academic year 2015/2016. (2) Relationship between the grading is based on Multiple Intelligences Research (MIR) learning model audiotorial, visual, and kinesthetic in accordance with the intelligence of a child in MIM PK Kartasura the academic year 2015/2016. Methods of data collection in this study is by observation, interview, and documentation. This research was a case study is to analyze in running in-depth study to identify subjects in a way summed up as a result of the analysis. The results showed that, (1) Implementation of Multiple Intelligences Research (MIR) in the grouping of classes in MI Muhammadiyah PK Kartasura, done by presenting the foster parents and the students concerned to be interviewed about the habits of children through Interviewer in collaboration with Nex Edu Surabaya to know the intelligence of each child, all students can be accepted, including children with special needs (ABK), whereas in learning entirely by teacher with a good beginning of making Lesson Plan, choosing strategies, and select the media used the process of teaching supervised by the Principal and evaluated with the Guardian Angel , (2) Relationship between the grading is based on Multiple Intelligences Research (MIR) learning model audiotorial, visual, and kinesthetic in MI Muhammadiyah PK Kartasura who have different learning styles between classes, enables teachers to take action, make selecting strategies that fit the learning style ( visual, auditory, and kinesthetic) students, facilitate student receives course materials and accelerate the development of children's intelligence. It also enables easy interaction with students or student teachers with students. Keywords: Multiple Intelligences Research (MIR), Grouping, Learning Styles.